(untitled) - Bunthof, Christine J. (Netherlands, 2002)
The development of flow cytometry for bacteria is an important asset for microbiological research. The rapid novel mehtods described in this thesis provide possibilities for examination of fermentation processes and food products.
Keywords: Fluorescent probes,Flow cytometry,Microbial physiology,Đầu dò huỳnh quang,Đo dòng tế bào,Sinh lý của vi sinh vật